Starting in your mental pole position: hypnosis helps elite downhill Mountainbike athletes to reach their optimal racing mindset - Hoffmann, N.; Strahler, J.; Schmidt, B. (Frontiers in Psychology, 2024)
Introduction Downhill Mountain Biking is an extreme sport requiring high mental strength to perform on the best level in a competition with only one run to win the race. The substantial challenge here is to control automatic processes like competitive anxiety and stress. Hypnosis can address these automatic processes. We developed and evaluated a hypnosis audio-intervention to activate the optimal racing mindset.